2009
DOI: 10.1038/sj.bjc.6605141
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a protease-resistant insulin-like growth factor-binding protein-4 inhibits tumour growth in a murine model of breast cancer

Abstract: BACKGROUND: Insulin-like growth factor 1 (IGF1) promotes breast cancer and disease progression. Bioavailability of IGF1 is modulated by IGF-binding proteins (IGFBPs). IGFBP4 inhibits IGF1 activity but cleavage by pregnancy-associated plasma protein-A (PAPP-A) protease releases active IGF1. METHODS: Expression of IGF pathway components and PAPP-A was assessed by western blot or RT -PCR. IGFBP4 (dBP4) resistant to PAPP-A cleavage, but retaining IGF-binding capacity, was used to block IGF activity in vivo. 4T1.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 38 publications
3
58
0
1
Order By: Relevance
“…However, the combined delivery of IGF-1R siRNA+p53 plasmid, IGF-1R siRNA+Bcl-2 siRNA or Bcl-2 siRNA+p53 plasmid did not further improve the efficacy of cell killing except IGF-1R siRNA+Bcl-2 siRNA+p53 plasmid (p<0.01), which could be due to the interactions among IGF-1R, Bcl-2 and p53 signaling pathways as discussed above, leading to a synergistic effect in reducing cell viability. A similar finding was observed in 4T1 cells (Figure 2) which also possess IGF-1R [43,44] and bcl-2 [45], but are deficient of p53 [46,47], indicating that the seeming synergistic effect of IGF-1R siRNA+Bcl-2 siRNA+p53 plasmid (p<0.01) might be due to the concerted role of IGF-1R as well as Bcl-2 knockdown and overexpression of p53 gene. A statistically significant effect was also exerted by Bcl-2 siRNA+p53 plasmid (p<0.05) in comparison with the nanoparticle-treated cells.…”
Section: J Nanomed Nanotechnolsupporting
confidence: 59%
“…However, the combined delivery of IGF-1R siRNA+p53 plasmid, IGF-1R siRNA+Bcl-2 siRNA or Bcl-2 siRNA+p53 plasmid did not further improve the efficacy of cell killing except IGF-1R siRNA+Bcl-2 siRNA+p53 plasmid (p<0.01), which could be due to the interactions among IGF-1R, Bcl-2 and p53 signaling pathways as discussed above, leading to a synergistic effect in reducing cell viability. A similar finding was observed in 4T1 cells (Figure 2) which also possess IGF-1R [43,44] and bcl-2 [45], but are deficient of p53 [46,47], indicating that the seeming synergistic effect of IGF-1R siRNA+Bcl-2 siRNA+p53 plasmid (p<0.01) might be due to the concerted role of IGF-1R as well as Bcl-2 knockdown and overexpression of p53 gene. A statistically significant effect was also exerted by Bcl-2 siRNA+p53 plasmid (p<0.05) in comparison with the nanoparticle-treated cells.…”
Section: J Nanomed Nanotechnolsupporting
confidence: 59%
“…Studies of PAPP-A in human breast cancer, subsets of which are IGF-responsive [10], are limited. There is some evidence that PAPP-A plays a role in promoting breast cancer progression [11,12]. However, a recent study suggested that PAPP-A is epigenetically silenced in human breast cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that IGF-IR activity is important for maintaining cyclin D expression and cell cycle progression (Wilsbacher et al 2008) and that this can be mediated by IGF-IR-dependent PI3 K-Akt activity (Banudevi et al 2010). Also, aberrant metabolism of IGF-IR is associated with a number of cancers including prostate, colorectal, breast and brain (Coulter et al 2008;Ma et al 2010;Kaulfuss et al 2009;Ryan et al 2009). We found that Cu II (gtsm) was a potent inhibitor of IGF-IR expression in the presence or absence of IGF and that this effect was associated with loss of PI3 K expression and activation.…”
Section: Discussionmentioning
confidence: 96%